Levels of Physical Activity in the Adult Population of La Guajira, Colombia: A Focus on Ethnicity - Panciera-di-Zoppola, Yaina; Niño-Restrepo, Juan; Melo-Freile, José; Ortiz-Moncada, Rocío (Frontiers in Public Health, 2021)
The objective of this study is to analyze the physical activity levels among the population in the department of La Guajira, Colombia, according to the different ethnic groups and their sociodemographic factors. The dependent variable is physical activity (METs.min-1), with the relevant data being gathered through the completion of the short version of the International Physical Activity Questionnaire (IPAQ) by a non-probability sample of 251 people of ≥ 18 years of age. The independent variables are linked to the sociodemographic factors of: sex, age, social class, civil status, educational level and municipality of residence. The ethnic group was defined as Indigenous and Afro-Colombian, while the non-ethnic group was defined as White or Mestizo. The data collected was analyzed according to the population compliance with the World Health Organization’s (WHO) physical activity recommendations. Regression models were also made according to the selected sociodemographic variables in order to determine the likelihood of the population meeting the physical activity targets. The analysis found that 78.1% of La Guajira’s population complied with the physical activity recommendations. According to the results of the bivariate analysis, the population of ≥ 47 years of age (OR=0.49; 95% CI: (0.25–0.96)), and who had a primary education (OR=0.32; 95% CI: (0.17–0.62)) presented a lower probability of complying with the physical activity recommendations, while those who lived in large municipalities (Riohacha) displayed a larger probability of compliance (OR=2.16; 95% CI: (1.18-3.96)). The multivariate analysis prove that the Indigenous and Afro-Colombian people in a low social class are more likely to comply with the physical activity recommendations (ORad=4.88; 95% CI: (1.31–18.1)), while residing in a smaller municipality (Manaure) is associated with a lower probability of compliance (ORad=0.39; 95% CI: 0.16-0.91)). Furthermore, it was concluded that La Guajira’s educated population is active and that the level with which they comply with the physical activity recommendations is high, even when compared to the national and global results. Low social class stands out as the sociodemographic factor most associated with high physical activity among the ethnic population; the Afro-Colombians are more active than the Indigenous population.